Analisis Faktor-Faktor Yang Mempengaruhi Minat Berwirausaha Mahasiswa Program Studi Pendidikan Ekonomi Fakultas Ilmu Sosial dan Ekonomi Universitas Hamzanwadi - Rohaeniah Zein; Isfi Sholihah; Ahmad Zainuddin Fikri (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2020)
This study aims to analyze the factors that influence the interest in entrepreneurship in the Economic Education Study Program of the Faculty of Social and Economic Sciences, Hamzanwadi University. This type of research uses quantitative methods. The population of this study were all students of the Hanzanwadi University Economic Education Study Program, totaling 408 people. In taking the sample, the researcher used the simple random sampling technique. The data analysis technique uses Multiple Linear Regression and as a tool in data processing, namely using the SPSS 16 program. The results show that partially and simultaneously the variables of family environment, entrepreneurial education and capital have an effect on the interest in entrepreneurship in students of the Economic Education Study Program, Faculty of Social and Economic Sciences, University. Hamzanwadi, and the variable that has the greatest influence is the variable capital